The physiological responses and expression patterns of heat induced genes to elevated temperature of marine Chlorella from different latitudes / Bahram Barati - Bahram , Barati (2018)
The increased frequency of heat waves due to climate change threatens all organism. Microalgae form the basis of aquatic food webs, and high temperatures significantly impact their adaptation and survival. Algae respond to environmental changes by modulating their photosynthetic rates and biochemical composition, which is in turn regulated by their gene expression. In this study, the effects of elevated temperature on marine Chlorella originating from different latitudes were examined. Strains from the Antarctic, temperate zone, and the tropics were grown at various temperatures, ranging from 4 to 38, 18 to 38, and 28 to 40 °C, respectively. A pulse-amplitude modulated (PAM) fluorometer was used to assess their photosynthetic responses. In addition, the biochemical compositions, including lipid, protein, carbohydrate and fatty acids were profiled to evaluate changes induced by temperature treatments. Increasing the temperature from 35 to 38 °C for both Antarctic and temperate strains and from 38 to 40 °C for the tropical strain resulted in severe inhibition of photosynthesis, which in turn suppressed growth. The temperature causing severe stress for each strain was selected for stress and recovery treatments. At different time points, the expressions of the photosynthetic and fatty acid biosynthesis key genes were analysed during stress and recovery. All the strains demonstrated the ability to recover from different stress levels, however, the tropical strain recovered most rapidly, while the Antarctic strain reported the slowest recovery. The results confirmed that the thermal threshold for the analysed Chlorella strains temperature falls between 38 and 40 °C. The response of studied strains differed from one another. Chlorella-Ant and Chlorella-Trop exhibited photosynthetic genes during stress, revealing their remarkable capability for maintaining photosystem II’s main component (psbC). In Chlorella-Temp, photosynthetic genes were suppressed, while during recovery, it was up-regulated.